YOUTH ORGANIZATIONS OF THE OUN OF THE KAMIANETS-PODIL REGION IN THE STRATEGY OF THE UKRAINIAN MOVEMENT OF RESISTANCE TO THE SOVIET REGIME - YARYCH , Volodymyr (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
Annotation. The purpose of the study is to characterize the place of youth in the development of ideological practices of the Organization of Ukrainian Nationalists. Highlight the tasks of youth organizations, in particular youth groups in the territory of Kamianets-Podilskyi region. To evaluate youth organizations as one of the key elements of Ukrainian resistance in the coordinate system of the Ukrainian movement of resistance to the totalitarian regime. The research methodology is based on the principles of historicism, objectivity, comprehensiveness, integrity, systematicity, and methods of analysis and synthesis, historical-genetic, historical-comparative, historical-typological, problem-chronological. The scientific novelty lies in the fact that the author shows the connection between the activities of youth organizations and the implementation of the tasks of spreading and establishing centers of the national liberation movement by the Main Branch of the OUN. A number of archival sources and scientific intelligence testify to the active participation of young people in the struggle for independence and sovereignty of Ukraine. This can be clearly observed in the history of Ukraine starting from the Battle of Kruty and in the modern Russian-Ukrainian war. The article proves the importance of the functioning of youth organizations and the specifics of their activities and tasks. From the above, we can conclude that the youth played an important role in the struggle, development and functioning of the OUN, and at the same time strengthened the Ukrainian spirit and in the future was able to keep the desire to fight in their families and pass on the idea of Ukraine's independence to the future generation.